Social and behaviour change and communication strategy for scaling equitable access to rice and common beans quality seeds to smallholder farmers in Butaleja district, Eastern Uganda. Strategy Document. - Nchanji, Eileen; Bomuhangi, Allan; Amuda, Alex; Mikhala, Audrine; Lengewa, Catherine; Asea, Godfrey; Yila, Jummai; L’parnoi, Peter; Kinyota, Phillip; Echesa, Prisca (2024)
Background: To address the persistent challenge of limited access to quality agricultural inputs, particularly high-quality seeds in Uganda, a social and behavioral strategy was developed under the CGIAR Seed Equal Initiative activities under work package 6. Though agriculture serves as a cornerstone of Uganda’s economy, employing 70% of the labor force and covering half of the national land area. Smallholder farmers, comprising 90% of the farming community, face barriers to accessing quality seeds hindering agricultural productivity and food security. This activity was led by the International Rice Research Institute (IRRI) and the Alliance of Bioversity International and CIAT in collaboration with the Centre for Behaviour Change and Communication (CBCC), focuses on improving seed access in Eastern Uganda, with a specific emphasis on Butaleja District. We aimed to empower smallholder farmers, women, and youth, enhance seed access and utilization, and contribute to increased agricultural productivity, livelihoods, and food security in Butaleja District and beyond. By implementing evidence-based strategies and fostering collaboration among stakeholders, we aim to create an inclusive and sustainable seed system that benefits all members of the agricultural community. Methodology: The Social and Behavior Change (SBC) strategies were developed through an interactive, researched, and planned process aimed at changing individual behaviours and social conditions. It uses a wholistic systematic process, the socio-ecological model, and Social Behaviour Change approaches like community engagement, advocacy, Interpersonal communication and mass media. Key barriers from the study: The formative assessment conducted prior to project implementation revealed key challenges, including limited awareness of improved seed varieties, gender disparities in seed access, and insufficient seed producer capacity. Key findings include: • Limited adoption of improved rice and bean varieties among farmers, particularly women, and youth. • Challenges in seed access, including high costs, limited availability, and inadequate knowledge about seed varieties. • Socio-economic factors affecting seed adoption, such as land access, gender roles, and cultural norms.